"As We Have Always Done": Decolonizing the Tomaquag Museum's Collections Management Policy. Issue 1 (March 2022) - Spears, Lorén; Thompson, Amanda
As Executive Director of the Tomaquag Museum, an Indigenous-led organization currently located in Exeter, Rhode Island, Lorén Spears (Narragansett-Niantic) continues the work of reimagining how museums represent and serve Indigenous communities begun by the Indigenous women who held that role before her. Today, we might identify these practices as "decolonizing, " but, to invoke Leanne Betasamosake Simpson (Michi Saagiig Nishnaabeg), it is "as [they] have always done." For over sixty years, the Tomaquag Museum has engaged Indigenous Belongings from its collection in conjunction with cultural knowledge shared by Indigenous peoples to educate the public on Native history, culture, arts, and Traditional Ecological Knowledge (TEK) of Southern New England. This essay highlights the Tomaquag Museum's praxis for decolonizing its collections management policy, led by Spears' intellectual labor. It alternates Spears' words, excerpted from a conversation with scholar and museum professional Amanda Thompson (non-Native), with selections from the in-progress collections management policy. This format creates a narrative which highlights the history of the museum and its ongoing decolonizing practice and illustrates how policy language can be integral to the work of empowering Native people and transforming museum structures.